Trend and burden of ischemic stroke attributable to high body mass index in China from 1990 to 2021, with projection to 2044 - Ning Ding; Ruiwen Fan; Xiaohui Zhang; Jiacheng Zhang; Yutian Zhu; Xiyan Xin; Yang Ye (PLoS ONE, 2025)
Background Ischemic stroke (IS) poses a significant public health burden in China, with high body mass index (BMI) identified as a key risk factor. Despite this, the temporal trends and sex-specific burdens of IS attributable to high BMI remain insufficiently explored. This study examines the burden of IS linked to high BMI in China from 1990 to 2021 and projects future trends to 2044. Methods Drawing on data from the Global Burden of Disease Study 2021, we first employed correlation analysis to examine the association between high BMI exposure and IS incidence in China over a 30-year period. Subsequently, we quantified the mortality and disability-adjusted life years (DALYs) attributable to high BMI-related IS. Our analysis included comparative assessments with global and high-income country trends, complemented by sex-stratified and age-specific evaluations. Finally, we developed forecasting models to project disease burden trajectories through 2044. Results From 1990 to 2021, China’s age-standardized IS incidence initially rose before stabilizing, with males consistently exhibiting higher rates than females. High BMI exposure increased steadily and strongly correlated with IS incidence. Age-standardized mortality attributable to high BMI grew from 0.98 to 2.21 per 100,000, while DALYs more than doubled from 24.61 to 56.21 per 100,000, with males disproportionately affected. The elderly, particularly men, showed the steepest increases. Unlike global declines, China’s high BMI-attributable burdens rose. Projections suggest continued growth, reaching 4.05 (male) and 3.23 (female) mortality rates by 2044, with DALYs at 101.33 and 96.63 per 100,000 respectively. Conclusion High BMI contributes to a growing and sex-disparate burden of IS in China, with accelerated growth in older adults. Unlike high-income countries, China has not yet achieved declines in high BMI-attributable IS mortality and DALYs. Urgent public health interventions targeting BMI reduction, particularly in males and older populations, are needed to mitigate future burdens.